Co-delivery of curcumin and STAT3 siRNA using deformable cationic liposomes to treat skin cancer. (21st April 2017) - Jose, Anup; Labala, Suman; Venuganti, Venkata Vamsi Krishna
Abstract: Skin cancer is one of the most widely prevalent cancer types with over expression of multiple oncogenic signaling molecules including STAT3. Curcumin is a natural compound with effective anti-cancer properties. The objective of this work was to investigate the liposomal co-delivery of curcumin and STAT3 siRNA by non-invasive topical iontophoretic application to treat skin cancer. Curcumin was encapsulated in cationic liposomes and then complexed with STAT3 siRNA. The liposomal nanocomplex was characterized for particle size, zeta-potential, drug release and stability. Human epidermoid (A431) cancer cells were used to study the cell uptake, growth inhibition and apoptosis induction of curcumin-loaded liposome–siRNA complex. Topical iontophoresis was applied to study the skin penetration of nanocomplex in excised porcine skin model. Results showed that curcumin-loaded liposome–siRNA complex was rapidly taken up by cells preferentially through clathrin-mediated endocytosis pathway. The co-delivery of curcumin and STAT3 siRNA using liposomes resulted in significantly ( p < .05) greater cancer cell growth inhibition and apoptosis events compared with neat curcumin and free STAT3 siRNA treatment. Furthermore, topical iontophoresis application enhanced skin penetration of nanocomplex to penetrate viable epidermis. In conclusion, cationic liposomal system can be developed for non-invasive iontophoretic co-delivery of curcumin and siRNA to treat skin cancer.